DEVELOPING ENGLISH WRITING MATERIALS IN NARRATIVE TEXT FOR THE EIGHTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Royanti Rajagukguk; Willem Saragih; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2018)
This research aims to develop the English writing materialsin Narrative text for the Eighth Grade Students of Junior High School by using picture series. This study was conducted using R & D method of Borg & Gall (2003). The research took place in SMP HKBP Pardamean Medan. The sample was the Eighth Grade Students that consisted of 29 students. The evaluators of the developed materials were two experts namely an English lecturer and an English teacher. There were some instruments that were applied in this study namely observation, questionnaire and interview. The finding of the study was the suitable English writing materials inNarrative text based on the students’ needs and level in SMP HKBP Pardamean Medan. The developed writing materials then were validated by the experts and it got 4,20 based on the highest interval of numerical scale was 5,00. In the form of percentage, it got 84% so it was categorized as “very good”. Therefore, it can be concluded that the developed English writing materials in Narrative text are appropriate to students’ needs and level and interesting for them. Automatically, it can be used for the Eighth Grade Students of Junior High School in teaching-learning activity in the classroom toincrease the students’ ability in writing Narrative text and motivate them in learning writing especially in Narrative Text. Keywords: Writing, Narrative text, Picture series, Research and Development ( R&D).